The World Trade Organization and World Customs Organization key conventions and agreements (TFA, HSC, RKC): membership trends and opportunities - Carsten Weerth (World Customs Journal, 2020)
The World Trade Organization (WTO) has 164 member states and its Trade Facilitation Agreement (WTO TFA) currently has 149 signatories. The World Customs Organization (WCO) has 183 member states and its most successful legal instrument-the Harmonized System Convention (HSC)-has 158 signatories, while its legal instrument for trade facilitation-the Revised Kyoto Convention (RKC)-has 120 signatories. This paper investigates which countries have signed which agreements and examines opportunities for future membership. It calls for WTO and WCO initiatives to attract new members to both organisations and their agreements.
Keywords: F53; K33; 330; Customs Law; Trade facilitation